2020
DOI: 10.1002/erv.2756
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and nutritional correlates of objectively assessed physical activity in patients with anorexia nervosa

Abstract: Background Physical activity (PA) plays a role in the course of anorexia nervosa (AN). Objective To assess the association between PA, nutritional status and psychological parameters in patients with AN. Method Using a wearable activity monitor, PA was assessed in 60 female AN inpatients, by step count and time spent in 4 metabolic equivalent (MET)‐intensity levels: sedentary behaviour, light, moderate and vigorous PA. In addition, BMI, psychological (patient‐reported outcome questionnaires) and nutritional pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Thirty‐three papers were identified that used sensors to measure physical activity levels and energy expenditure (see Table 1). The majority of studies used accelerometers to measure physical activity (Alberti et al, 2013; Belak et al, 2017; Bezzina et al, 2019; Bratland‐Sanda et al, 2011, 2012; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010a; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010b; Bratland‐Sanda, Sundgot‐Borgen, Rosenvinge, et al, 2010; Carrera et al, 2012; Duriez, Guy‐Rubin, et al, 2021; El Ghoch et al, 2013, 2016; Grosser et al, 2020; Hofmann et al, 2017; Holtkamp et al, 2006; Kemmer et al, 2020; Keyes et al, 2015; Klein et al, 2007; Kolar et al, 2020; Lampe et al, 2021; Langlet et al, 2021; Lehmann et al, 2018; Martinez‐Sanchez et al, 2020; Mathisen, Bratland‐Sanda, et al, 2018; Mathisen, Rosenvinge, et al, 2018; McDuffie, 1998; Sauchelli et al, 2015; Stengel et al, 2017; van Elburg et al, 2007; Wons et al, 2021; Zeeck et al, 2020). Other sensors utilized include pedometers (Blinder et al, 1970; Crandall, 2004), multi‐sensor full‐body systems including the Intelligent Device for Energy Expenditure and Activity and the Tracmor physical activity sensor system (Bouten et al, 1996; Gianini et al, 2016; Harris et al, 2008), and indirect calorimeter (Bouten et al, 1996; Harris et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three papers were identified that used sensors to measure physical activity levels and energy expenditure (see Table 1). The majority of studies used accelerometers to measure physical activity (Alberti et al, 2013; Belak et al, 2017; Bezzina et al, 2019; Bratland‐Sanda et al, 2011, 2012; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010a; Bratland‐Sanda, Sundgot‐Borgen, Ro, et al, 2010b; Bratland‐Sanda, Sundgot‐Borgen, Rosenvinge, et al, 2010; Carrera et al, 2012; Duriez, Guy‐Rubin, et al, 2021; El Ghoch et al, 2013, 2016; Grosser et al, 2020; Hofmann et al, 2017; Holtkamp et al, 2006; Kemmer et al, 2020; Keyes et al, 2015; Klein et al, 2007; Kolar et al, 2020; Lampe et al, 2021; Langlet et al, 2021; Lehmann et al, 2018; Martinez‐Sanchez et al, 2020; Mathisen, Bratland‐Sanda, et al, 2018; Mathisen, Rosenvinge, et al, 2018; McDuffie, 1998; Sauchelli et al, 2015; Stengel et al, 2017; van Elburg et al, 2007; Wons et al, 2021; Zeeck et al, 2020). Other sensors utilized include pedometers (Blinder et al, 1970; Crandall, 2004), multi‐sensor full‐body systems including the Intelligent Device for Energy Expenditure and Activity and the Tracmor physical activity sensor system (Bouten et al, 1996; Gianini et al, 2016; Harris et al, 2008), and indirect calorimeter (Bouten et al, 1996; Harris et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding ED treatment and acceleration, Gianini et al (2016) found AN inpatients had increased acceleration after weight restoration and at 1-month follow-up. Differently, Grosser et al (2020) found greater acceleration in AN at lower weights, and Yoshida and colleagues (2006) found no changes in acceleration after AN patients completed refeeding.…”
Section: Acceleration and Anmentioning
confidence: 95%
“…Seven studies investigated time spent sedentary. Five of these reviewed patients with AN [21][22][23][24][25] and two [26,27] assessed those with an oncology diagnosis. People with an oncology diagnosis ranged from 1219-1412 minutes sedentary per day.…”
Section: Sedentary Timementioning
confidence: 99%